2017
DOI: 10.1021/acsami.7b04599
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Graphene Film as Low Friction Solid Lubricant in Macroscale Contact

Abstract: Promoted by the demand for solid lubricants, graphene has been proved to be a promising material for potential applications in reducing friction and wear. Here, a novel lubricating system where graphene sliding against graphene is developed to achieve low friction in macroscale contact. And the large area graphene film used here were prepared by a unique self-assembly technique based on Marangoni effect. Low friction coefficient of about 0.05 is obtained, and it is demonstrated that the film thickness, applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 108 publications
(48 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…They concluded that nanoscrolls slide on a diamondlike carbon surface at which incommensurate contact occurs, thereby reducing the friction coefficient. Wu et al [62] developed a lubricating system in which a self-assembled graphene film (SGF) slides against an SGF under macroscale contact. Ultra-low friction was discovered owing to the low resistance to shear between the adjacent layers of SGFs.…”
Section: Interlaminar Friction In Homogeneous and Heterogeneous Slidimentioning
confidence: 99%
“…They concluded that nanoscrolls slide on a diamondlike carbon surface at which incommensurate contact occurs, thereby reducing the friction coefficient. Wu et al [62] developed a lubricating system in which a self-assembled graphene film (SGF) slides against an SGF under macroscale contact. Ultra-low friction was discovered owing to the low resistance to shear between the adjacent layers of SGFs.…”
Section: Interlaminar Friction In Homogeneous and Heterogeneous Slidimentioning
confidence: 99%
“…Some studies [17][18][19] explored the sliding behaviour of graphene nanoflakes on a graphene surface at the microscale level using scanning tunnelling microscopy, finding a superlubric state of graphene at low temperatures [20]. Many other studies [21][22][23][24][25][26][27][28][29][30] reported that graphene sheets exhibited excellent macroscale tribological properties on various surfaces of friction pairs, such as silicon-like substrates [21][22][23][24], mica [25], iron [26], copper [27,28], and steel [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, a layered material composed of carbon atoms structured on a hexagonal lattice, has attracted much attention in the scientific community 1 , being a candidate for the fabrication of electronic devices 2 , gas sensors 3 as well as micro- and nano-electromechanical systems (MEMS and NEMS, respectively) 4,5 . Although the tribological properties of graphene have not yet been fully understood, the usage of graphene as both solid lubricant and coating has been proposed 610 . Studying friction in graphene becomes even more relevant as tribological properties of nanoscale materials might differ considerably from their bulk counterparts 11 , presenting novel and unexpected features.…”
Section: Introductionmentioning
confidence: 99%